Mastering derivatives - Mahat, Aishah; Putra Muhamad, Muhamad Yadiy; Abd Naddin, Ahmad Fawzan; Shahrin, Ikhwan Syahmi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Engineering students are required to pass a calculus course, with a significant focus on the topic of differentiation. However, many students struggle with this concept, resulting in lower scores and a lack of confidence in solving mathematical problems. These challenges can affect their overall academic performance and future learning. To address this, a teaching aid called Mastering Derivatives has been developed. This resource is designed to help students overcome difficulties in mathematics and create a more engaging learning environment. Mastering Derivatives provides concise notes and essential formulas for each subtopic, making it easier for students to grasp and apply calculus concepts. Additionally, it includes a range of questions—beginner, intermediate, and advanced—intended to enhance problem-solving skills and comprehension, especially for those struggling in the subject. Although primarily targeted at students from UiTM’s Faculty of Engineering enrolled in Calculus I, Mastering Derivatives is particularly beneficial for those who performed poorly in Assessment 1. With this digital tool, it is hoped that both lecturers and students will experience an improved teaching and learning experience, leading to better academic outcomes.